Types of Fi'il in Surah Al-Muddatsir and Learning Using The Cooperative Learning Model - Hana, Sada; Ni’mah , Fitri Maulin; Mudzakir, Muhammad Wafiq; Hakiki, Ikhfanul; Faizun, Ahmad (DAS Institute, 2023)
This research aims to find fi'il (verbs including fi'il madhi, the past form of the verb, fi'il mudhori' the present or done verb, fi'il amr, the command form of the verb in Surah Al-Muddatsir and determine the appropriate learning techniques easy to use. This research uses a qualitative approach with a library research type. Data analysis in this research uses the Milles and Huberman technique. Based on the data analysis that has been carried out there are 68 fi'il or verbs which are divided into fi'il madhi, fi'il mudhori' and fi'il amr, based on researchers' findings, the verb or fi'il has various forms in each verse, with a variety of fi'il forms, cooperative learning techniques are suitable for studying them.